Identifikasi Batuan Pembentuk Air Asam Tambang Pada Pit Mayang Menggunakan Uji Statik di PT Menara Cipta Mulia: Identification Of Acid Mine Water-Forming Rocks In Pit Mayang Using Static Tests At PT Menara Cipta Mulia - Aulia, Nur Fajri; Andini, Delita Ega; Pitulima, Janiar; Tono, E.P.S.B. Taman (Program Studi Teknik Pertambangan Universitas Bangka Belitung, 2025)
Mine Acid Water is one of the impacts of the mining industry that must be handled seriously because it can cause environmental quality degradation. The factor for the formation of AAT is due to the presence of sulfide minerals in the rock. It is necessary to prevent the formation of AAT by identifying rocks that are Potential Acid Forming (PAF) and Non Acid Forming (NAF). Identification of an AAT is carried out by static test. The research method uses quantitative data in the form of rock sampling with full coring drilling and conducting static tests in the laboratory. The results of this study were M01 samples (white sandstone) with ANC values of 1.7 KgH2SO4 /ton, NAG pH 6.63, Total Sulfur <0.01%, pH of paste 7.22 and NAPP -1.4 KgH2SO4 /ton. The sample was M02 (sand) with ANC value of 1 KgH2SO4 /ton, NAG pH 6.63, Total Sulfur <0.01%, pH of paste 7.37 and NAPP -0.7 KgH2SO4 /ton. The sample was M03 (black sandstone) with ANC value of 1.4 KgH2SO4 /ton, NAG pH 4.41, Total Sulfur 0.06%, pasta pH 6.89 and NAPP 0.4 KgH2SO4 /ton. The geochemical identification of rocks at PT Menara Cipta Mulia has 2 samples, namely M01 (white sandstone) and M02 (sand) samples that are Non Acid Forming (NAF) and 1 sample, namely M03 (black sandstone) samples that are Potential Acid Forming (PAF).